WebSphere MQ primer : an introduction to messaging and WebSphere MQ - Taylor, Mark E. (IBM redbooks., 2012)
The power of IBM® WebSphere® MQ is its flexibility combined with reliability, scalability, and security. This flexibility provides a large number of design and implementation choices. Making informed decisions from this range of choices can simplify the development of applications and the administration of a WebSphere MQ messaging infrastructure. Applications that access a WebSphere MQ infrastructure can be developed using a wide range of programming paradigms and languages. These applications can run within a substantial array of software and hardware environments. Customers can use WebSphere MQ to integrate and extend the capabilities of existing and varied infrastructures in the information technology (IT) system of a business. This IBM Redpaper™ publication provides an introduction to message-oriented middleware to anyone who wants to understand messaging and WebSphere MQ. It covers the concepts of messaging and how WebSphere MQ implements those concepts. It helps you understand the business value of WebSphere MQ. It provides introductory information to help you get started with WebSphere MQ. No previous knowledge of the product and messaging technologies is assumed.